Students’ and lecturers’ perception on the use of introductory engineering mathematics PutraMOOC - Mokhtar, Makhfudzah; Wan Adnan, Wan Azizun; Mohd Harithuddin, Ahmad Salahuddin; Jamaludin, Diyana; Zan, Zuraidah; Ahmad, Faisul Arif (Penerbit UTM Press, 2022)
This paper presents the perceptions of lecturers and students on the use of the Introductory Engineering Mathematics PutraMOOC as a medium of learning and teaching for first year engineering students. The objectives of the study include respondents' perceptions of the characteristics of the PutraMOOC and its impact on the implementation of OBE. To measure the findings based on the respondents' experience on using the PutraMOOC, questionnaires which was also linked to students' scores, as well as interviews with lecturers were conducted. The results of this study show a positive impact and perception of the use of the PutraMOOC. However, based on the findings, there are also some improvements that need to be made in helping the effectiveness of the PutraMOOC in the future use.